2002
DOI: 10.1101/gr.80202
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Regulated Transcription in the Pathogenic Fungus Cryptococcus neoformans

Abstract: The basidiomycete fungus Cryptococcus neoformans is an opportunistic pathogen of worldwide importance that causes meningitis, leading to death in immunocompromised individuals. Unlike many basidiomycete fungi, C. neoformans is thermotolerant, and its ability to grow at 37°C is considered to be a virulence factor. We used serial analysis of gene expression (SAGE) to characterize the transcriptomes of C. neoformans strains that represent two varieties with different polysaccharide capsule serotypes. These includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
75
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 59 publications
7
75
0
3
Order By: Relevance
“…We compared our array data of the WT strain to those from other microarray analyses performed independently to identify temperature-regulated or heat-shock responsive genes in C. neoformans (Steen et al 2002;Kraus et al 2004;Chow et al 2007). Steen et al (2002) demonstrated that the tag representing cyclophilin A (CPA1 and CPA2) is expressed at higher levels at 37°than at 25°.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared our array data of the WT strain to those from other microarray analyses performed independently to identify temperature-regulated or heat-shock responsive genes in C. neoformans (Steen et al 2002;Kraus et al 2004;Chow et al 2007). Steen et al (2002) demonstrated that the tag representing cyclophilin A (CPA1 and CPA2) is expressed at higher levels at 37°than at 25°.…”
Section: Discussionmentioning
confidence: 99%
“…Steen et al (2002) demonstrated that the tag representing cyclophilin A (CPA1 and CPA2) is expressed at higher levels at 37°than at 25°. Our array data also confirmed this finding (Table S3 and Table S4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unifying characteristics of the pathogenic cryptococci include the production of a polysaccharide capsule, the ability to form melanin pigments through the activity of the multicopper oxidase laccase, and the ability to adapt to and thrive at mammalian host temperature. Adaptation of C. neoformans to the host temperature is accompanied by major changes in gene expression as measured by microarray analysis and serial analysis of gene expression (SAGE) (5,19,29). This modulation of gene expression likely requires alterations in mRNA synthesis rates through activation of transcriptional transactivators and repressors, as well as alterations in chromatin structure.…”
mentioning
confidence: 99%
“…Molecular biologists regularly apply acute insults to provoke dramatic molecular responses that are easy to assay 19 Hsp90 negatively regulates hyphal development in C. albicans (ca). 24 temperature upshifts also induce HSP90 expression in C. neoformans (cn), H. capsulatum (Hc) and P. brasiliensis (Pb) [31][32][33] and promote yeast growth rather than hyphal development in these fungi. this raises the possibility that Hsp90 might also regulate morphogenesis in these pathogenic fungi (see text).…”
Section: Article Addendummentioning
confidence: 99%